2021
DOI: 10.3906/sag-2006-173
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of noncritical COVID-19 patients with early hospitalization and early antiviral treatment outside the ICU

Abstract: Background/aim: Despite the COVID-19 pandemic has been going on over 5 months, there is yet to be a standart management policy for all patients including to those mild-to-moderate cases. We evaluated the role of early hospitalization in combination with early antiviral therapy with COVID-19 patients in a tertiary care university hospital. Materials and Methods: This was a prospective, observational, single center study on probable/confirmed COVID-19 patients hospitalized in a tertiary care hospital COVID-19 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…This can be explained by the fact that, unlike others, mild patients without pneumonia were not included in our study. The ratio of the patients aged over 65 years was also higher than the ratio in previous studies, which scrutinized clinical outcomes of the patients from China and Turkey (11)(12)(13)(14). The mean age of the patients and the ratio of the patients' aged over 65 years were found to be significantly higher in patients with severe disease similar to other studies (11,14,15).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This can be explained by the fact that, unlike others, mild patients without pneumonia were not included in our study. The ratio of the patients aged over 65 years was also higher than the ratio in previous studies, which scrutinized clinical outcomes of the patients from China and Turkey (11)(12)(13)(14). The mean age of the patients and the ratio of the patients' aged over 65 years were found to be significantly higher in patients with severe disease similar to other studies (11,14,15).…”
Section: Discussionsupporting
confidence: 74%
“…However, this could be due to the fact that they included the patients without pneumonia in their analyses and also the comorbidity rate was lower in these studies (14,15). Hypertension and diabetes mellitus were the leading comorbidities in our study as shown in previous studies, also the frequency of chronic obstructive pulmonary disease (COPD) was higher than all (11,13,16,(19)(20)(21)(22). Unlike other studies, the frequency of obesity and malignancy was lower (7,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Among the 11 studies, three studies were RCTs [16,[18][19][20], one study was a non-randomized controlled study [17], one study was a before and after nonrandomized controlled study [21], and six studies were observational studies or case series [22][23][24][25][26]. Among the comparative studies, the comparators included umifenovir [17], baloxavir marboxil [18], standard of care (SOC) [19], lopinavir/ritonavir [21], and HQ alone or in combination with azithromycin [25]. An RCT that examined the early or late initiation of favipiravir treatment was the only study investigating asymptomatic or mildly ill patients [19].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The rate of patients who needed intensive care has been reported to be 5-15.7% in different studies. 2,3,18,22,25,41,42 Mortality varies from 2.08% to 78% in patients with COVID-19 disease 12,14,15,21,24,41,42 , and from 1.4% to 72% among ICU patients with COVID-19. 3,4,16,17,27 In the studies conducted in our country, mortality rates between 2.08 and 10.5% 26,27,41,42 have been reported.…”
Section: Discussionmentioning
confidence: 99%